2001
DOI: 10.1557/proc-671-m4.9
|View full text |Cite
|
Sign up to set email alerts
|

Wafer Nanotopography Effects on CMP: Experimental Validation of Modeling Methods

Abstract: Nanotopography refers to 10-100 nm surface height variations that exist on a lateral millimeter length scale on unpatterned silicon wafers. Chemical mechanical polishing (CMP) of deposited or grown films (e.g., oxide or nitride) on such wafers can generate undesirable film thinning which can be of substantial concern in shallow trench isolation (STI) manufacturability. Proper simulation of the effect of nanotopography on post-CMP film thickness is needed to help in the measurement, analysis, diagnosis, and cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…Experimental data used here is taken from previously reported studies on nanotopography [1]. The experiment consists of 8 identical sets of 200 mm epi wafers, each set containing wafers with five different nanotopography signatures.…”
Section: Experimental Description and Simulation Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental data used here is taken from previously reported studies on nanotopography [1]. The experiment consists of 8 identical sets of 200 mm epi wafers, each set containing wafers with five different nanotopography signatures.…”
Section: Experimental Description and Simulation Resultsmentioning
confidence: 99%
“…Previous work has shown that substantial film thinning can result from the polishing of films on wafers with certain underlying nanotopography signatures [1,3,4] as illustrated in Fig. 2.…”
Section: Introductionmentioning
confidence: 99%
“…Several specialized systems have been developed for measuring nanotopography, including scanning laser systems as well as interferometric systems that use a white light halogen source [18]. In the nanotopography studies discussed above, 200-and 300-mm wafers have been measured using a commercial laser scanning system (ADE SQM), [19], as well as a commercial white light interferometric system (ADE Phase-Shift Nanomapper), [10], [13]- [15]. A system that uses a Schack-Hartman wavefront sensor has also been reported [20].…”
Section: B Nanotopographymentioning
confidence: 99%
“…For unpatterned rigid silicon substrates, waviness is defined as nanometer-scale surface height variation on a lateral millimeter-length scale. 7 For polymer substrates, the pressure applied onto the substrate affect the waviness. When nanoimprint lithography is used to pattern flexible substrates, having insight about the effect of the pressure on waviness of the flexible substrate is necessary.…”
Section: Introductionmentioning
confidence: 99%